Impact of orange juice consumption on cardiovascular disease risk factors: a systematic review and meta-analysis of randomized-controlled trials. Issue 12 (22nd April 2022) - Alhabeeb, Habeeb; Sohouli, Mohammad Hassan; Lari, Abolfazl; Fatahi, Somaye; Shidfar, Farzad; Alomar, Osama; Salem, Hany; Al-Badawi, Ismail A.; Abu-Zaid, Ahmed
Abstract: Cardiovascular disease (CVD) is the greatest cause of premature death and disability globally. Numerous therapeutic strategies have been developed to improve and prevent the adverse cardiovascular events, including nutritional approaches. This systematic review and meta-analysis summarized the evidence on orange juice consumption on CVD risk factors. Four databases were searched up to September 2020. Ten randomized controlled trials were included in the final analysis. Pooled results demonstrated a significant effect of orange juice on glucose (WMD: −2.92 mg/dl, 95% CI: −5.327, −0.530, p = 0.017), insulin (WMD: −1.229 μU/ml, 95% CI: −2.083, −0.374, p = 0.005), HOMA-IR (WMD: −0.464, 95% CI: −0.747, −0.181, p = 0.001), total cholesterol (WMD: −9.84 mg/dl, 95% CI: −15.43, −4.24, p = 0.001), LDL-C (WMD: −9.14 mg/dl, 95% CI: −15.79, −2.49, p = 0.007), and CRP (WMD: −0.467 mg/l, 95% CI: −0.815, −0.120, p = 0.008) compared to control group. However, the effect of orange juice on body composition factors and other CVD risk factors was not significant compared to control group. These lowering effects of glucose, HOMA-IR, total cholesterol, and LDL-C were robust in subgroups with orange juice consumption ≥500 ml/day. This meta-analysis suggests that orange juice may be beneficial in improving several CVD risk factors.